(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2015)
In this paper, the main topic will be the financing of utility companies and the financial impact on the budget of the local business units. A special emphasis will be placed on the financing of utility companies in Slavonski Brod. The paper defines each area of utility services and presents the utilities as services of public interest as well their privatization in general. The paper reports on the financing of these services and on the European Union regulations and directives concerning them. In addition, the paper includes an overview of the sources of funding of utility companies and loan opportunities. Guarantees and subsidies are included as financing measures of the activities of communal companies. The practical part presents an interview with key individuals of the city of Slavonski Brod with regard to the impact of the budget on the financing of utility services of the utility company in this city – "Komunalac Ltd.". Keywords: Utility companies, financing, Slavonski Brod city, "Komunalac Ltd.", budget, public interest